2014
DOI: 10.7567/jjap.53.036503
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic effects in 11 nm imaging of extreme ultraviolet lithography with chemically amplified resists

Abstract: The resolution of extreme ultraviolet (EUV) lithography with chemically amplified resist processes has reached 16 nm (half-pitch). The development of chemically amplified resists is ongoing toward the 11 nm node. However, the stochastic effects are increasingly becoming a significant concern with the continuing shrinkage of features. In this study, the fluctuation of protected unit distribution caused by the stochastic effects during image formation was investigated assuming line-and-space patterns with 11 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The simulation results were compared with LER of line-andspace patterns with 11-32 nm half-pitch, that was recalculated on the basis of the results of previous studies. 29,30) The feasibility of sub-10-nm half-pitch fabrication with EUV lithography is discussed from the viewpoint of resolution and LER without assuming any required sensitivities, considering the potential performance of state-of-the-art EUV resists.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results were compared with LER of line-andspace patterns with 11-32 nm half-pitch, that was recalculated on the basis of the results of previous studies. 29,30) The feasibility of sub-10-nm half-pitch fabrication with EUV lithography is discussed from the viewpoint of resolution and LER without assuming any required sensitivities, considering the potential performance of state-of-the-art EUV resists.…”
Section: Introductionmentioning
confidence: 99%
“…30) The relationships between LER, chemical gradient, and stochastic effect have been discussed in detail elsewhere. [35][36][37][38] On the other hand, stochastic defect generation is related to the protected unit fluctuation at x = «p 1/2 and 0. The dependence of the protected unit fluctuation at x = «p 1/2 and 0 on the half-pitch has also been discussed in detail in a previous study.…”
Section: Resultsmentioning
confidence: 99%
“…[26] The relationships among LER, the chemical gradient, and the stochastic effect have been discussed in detail. [31][32][33][34] The fluctuation in the number of protected units near the center of the line pattern leads to the generation of pinching. [18] It has been reported that the elimination of pinching is important for the development of chemically amplified resists with sub-15 nm resolution.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…The final standard deviations at ±p 1/2 /2 were 2.80, 2.89, and 3.17, respectively. LER was calculated to be 2.07, 2.14, and 2.34 nm for σ i =0, In our previous studies, [31][32][33][34][35] we have discussed the latent image quality including the protected unit fluctuation mainly assuming an acid generator concentration of 10 wt% in a TPS-Tf equivalent and an effective reaction radius of 0.1 nm for deprotection. The corresponding quantum efficiency was 2.0.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%